Status ketersediaan makanan dan status gizi ibu sebagai faktor risiko kegemukan pada anak prasekolah - Yunita Indah Prasetyaningrum; Nyoman Kertia; I Made Alit Gunawan (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: Childhood obesity is a strong predictor of adult obesity incidence and can increase risk factors for getting chronic diseases. The causes of obesity are multifactor, determined by genetic and food environment changes. Risk factors believed to be the cause of obesity are home food availability status and maternal obesity.Objective: To analyze the risk of home food availability status and maternal obesity to obesity in preschool children aged 3-5 years. Method: This study was a matched case-control study. The case of this study was obese preschool children (Z-score WHZ > 2 SD) and control of this study was non-obese preschool children (Z-score WHZ -2 ≤ SD ≤ 2). Control group was taken by an age and gender matching with the case group. Based on the nutritional status screening result of 53 early childhood education (ECD) schools on 13 sub-districts in Kota Yogyakarta, there were 101 obese children and 101 non-obese children. Those schools were chosen by cluster sampling method and PPS (Probability Proportional to Size). Besides, information about home food availability status and maternal obesity was collected using questionnaire. The data were analyzed using McNemar test and conditional logistic regression. Results: Home food availability status (OR = 1.85; p=0.03; 95% CI=1.08-3.16) and maternal obesity (OR=2.5; p=0.003; 95% CI=1.37-4.55) were the most dominant risk factor related to the incidence of obesity in preschool children aged 3-5 years.Conclusion: Home food availability status and maternal obesity significantly increase the risk for getting obese in preschool children aged 3-5 years.